Green logistics in food distribution - a case study - Helo, Petri; Ala-Harja, Hanne (Taylor & Francis, 2018)
Environmental impacts, such as Green House gas emissions, have been introduced to supply chain management as an additional parameter to traditional key performance indicators such as cost, lead-time and on-time delivery. This paper analyses a case example from the food industry on how CO2 emissions are structured in a value chain. The focus of the analysis covers food factory order-picking operations, transportation, warehousing and distribution aspects. The paper aims to demonstrate greening and CO2 saving potential areas of development for thermo-controlled food logistics. The results show the energy-saving potential of several supply chain processes giving examples of distribution logistic online-temperature controlling possibilities. Greening decisions in supply chain design in the food industry are considered.
Keywords: supply chain management; green logistics; food industry; fi=Tuotantotalous|en=Industrial Management|